2011
DOI: 10.1002/hup.1180
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive effects of kava (Piper methysticum): a systematic review

Abstract: The majority of evidence suggests that kava has no replicated significant negative effects on cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 47 publications
3
36
0
Order By: Relevance
“…They reported that due to a lack of consistency in “study designs and use of control” (p. 108), it was found difficult to establish the psychopharmacological effects of kava. For instance, LaPorte et al () suggested acute kava use, both significantly impaired visual attention and increased body sway, whereas in another study, it was reported that: “kava significantly enhanced visual attention and working memory” (p. 110). They concluded: “kava has non‐deleterious effects on cognition during acute administration or produces reduced visual attention at higher doses during cognitive demand” (p. 110).…”
Section: Kava and Cognition Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported that due to a lack of consistency in “study designs and use of control” (p. 108), it was found difficult to establish the psychopharmacological effects of kava. For instance, LaPorte et al () suggested acute kava use, both significantly impaired visual attention and increased body sway, whereas in another study, it was reported that: “kava significantly enhanced visual attention and working memory” (p. 110). They concluded: “kava has non‐deleterious effects on cognition during acute administration or produces reduced visual attention at higher doses during cognitive demand” (p. 110).…”
Section: Kava and Cognition Functionmentioning
confidence: 99%
“…The first systematic review to assess the effects of kava on cognition was undertaken by LaPorte, Sarris, Stough, and Scholey (). They reported that due to a lack of consistency in “study designs and use of control” (p. 108), it was found difficult to establish the psychopharmacological effects of kava.…”
Section: Kava and Cognition Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review of 10 clinical trials, the impact of kava on neurocognition was explored . There were 7 small, randomized controlled trials assessing the cognitive impact of acute kava ingestion, while only 1 small, randomized controlled trial and 2 case control studies assessed chronic kava use.…”
Section: Kava's Safety Profilementioning
confidence: 99%
“…Kavalactones have been shown to exhibit only moderate antioxidant activity [13], Several other effects have been reported, such as inhibition of nuclear factor-κB [14], iNOS [15] and cyclooxygenases [13], and neuroprotection after focal cerebral ischemia in mice and rats [16]. Furthermore, kava has no significant negative effects on cognition [17]. Yet, no interactions between kavalactones and neuroreceptors have been found that would explain the various pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%